2016
DOI: 10.5704/moj.1611.005
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study to compare Intra-articular versus Intravenous Tranexemic Acid in reducing Post-operative Blood Loss in staged bilateral Total Knee Arthroplasty

Abstract: Introduction:Tibial plateau injury involves the articular surface of the proximal tibia with diverse group of fractures that represent a wide spectrum of severity that challenge even the most experienced surgeons, but with the invent of modern diagnostic technology and the advent of locking plates, results appear to be improving over time. Method: The study was conducted on thirty patients admitted in the department of orthopaedics with diagnoses of tibial plateau fractures treated with Locking Condylar Plate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Previous studies have found similar results in various procedures showing the effects of TXA in improving hemostasis. 40–43 In this study, low dose TXA demonstrates lower rates of complications and provides efficacy for hemostasis during craniosynostosis surgery. However, at this time, further research is required to reduce the uncertainty given study heterogeneity for recommendations to be provided.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have found similar results in various procedures showing the effects of TXA in improving hemostasis. 40–43 In this study, low dose TXA demonstrates lower rates of complications and provides efficacy for hemostasis during craniosynostosis surgery. However, at this time, further research is required to reduce the uncertainty given study heterogeneity for recommendations to be provided.…”
Section: Discussionmentioning
confidence: 91%